Perioperative Anesthetic and Surgical Complications of the Nuss Procedure - BOSTANCI, KORKUT; UMUROĞLU, TÜMAY (W B SAUNDERS CO-ELSEVIER INC, 2013)
Objective: The Nuss procedure is a chest wall remodeling surgery performed in patients with pectus excavatum. This study was performed to analyze perioperative surgical and anesthetic complications with the Nuss procedures. Design: A retrospective analysis. Setting: An academic hospital. Participants: Two hundred fourteen patients (children, adolescents, and adults) undergoing the Nuss procedure over 6 years. Interventions: Patient age and sex, premorbid diseases, indications for surgery, patient position during the procedure, the length of surgery, time to hospital discharge, postoperative analgesia method, and the presence of perioperative complications were recorded. Measurements: No mortality was observed. The overall complication rate was 18.7%, but the overall event rate was 42.6% (91 events in 40 patients). Intraoperative hypotension, tachycardia, and hypercapnia were the most common complications (4.7%), followed by postoperative ileus (3.2%), pneumothorax (right, left, or bilateral; 4.2%), lung parenchymal laceration (2.3%), and postoperative nausea and vomiting (2.3%). Two patients had an ulnar nerve palsy and 1 patient had a brachial nerve palsy as a result of surgical position. Conclusion: Although the Nuss procedure is reported to be minimally invasive, some serious complications concerning both surgery and anesthesia should not be overlooked. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: pectus excavatum; chest wall deformity; Nuss procedure; Nuss operation; minimally invasive surgery; complication; anesthesia; MINIMALLY INVASIVE REPAIR; PECTUS EXCAVATUM; PULMONARY-FUNCTION; EXPERIENCE; SURGERY